Functional immune diversity in reindeer reveals a high Arctic population at risk - Lukacs, Morten; Nymo, Ingebjørg H.; Madslien, Knut; Våge, Jørn; Veiberg, Vebjørn; Rolandsen, Christer Moe; Bøe, Cathrine Arnason; Sundaram, Arvind Y. M.; Grimholt, Unni (Frontiers in Ecology and Evolution, 2023)
Climate changes the geographic range of both species as well as pathogens, causing a potential increase in the vulnerability of populations or species with limited genetic diversity. With advances in high throughput sequencing (HTS) technologies, we can now define the genetic diversity of wild species at a larger scale and identify populations at risk. Previous studies have used genomic DNA to define Major histocompatibility complex (MHC) class II diversity in reindeer. Varying numbers of expressed genes found in many ungulates strongly argues for using cDNA in MHC typing strategies. We have used available reindeer genomes to identify candidate genes and established a HTS approach to define expressed MHC class I and class II diversity. To capture a broad diversity we included samples from wild reindeer from Southern Norway, semi-domesticated reindeer from Northern Norway and reindeer from the high Artic archipelago Svalbard. Collectively our data show a medium MHC diversity in semi-domesticated and wild Norwegian mainland reindeer, and low MHC diversity reindeer from Svalbard. Reindeer from Svalbard have experienced a severe bottleneck, but although the population size have increased in recent years, the immune diversity has not increased. Consequently, Svalbard reindeer thus have a very low MHC diversity, placing them at risk if the pathogenic pressure changes.